Paypal Analysis as e-Payment in The e-Business Development - Nomi Br Sinulingga (International Conference on Engineering and Technology Development (ICETD), 2012)
Development of the Internet encourages the movement of traditional business to electronic business (e-business). Internet has change the business and make range of services more widely. Internet enables anyone running business with the prospective buyers from all over the world. Internet will help business local to find supplier from local or other countries more easily, there for the business will run more simple. E-business enables buyers and sellers running business without face to face, but communication and transactions can be done electronically. All this activities can be done through the Internet. Most of business people has not been using the internet as a business media especially in Sumatera. Whereas there are a lot of commodity come from Sumatera that can be sold to overseas markets.A few business people do not using the internet while running their business transaction. They does not looking for the supplier by using the internet. For example, through internet business people could directly purchase goods from China which is more cheaper than Indonesia. All these processes can be done through the internet. It is Very easy to find products or selling products on the Internet. But often the difficulty is how to make the payment process for all transactions. Bank has a very important role in the payment process. For domestic payments can easily be done through Bank transfer, transfer via ATM, Internet banking and SMS banking. However, to process payments from or to overseas, banks process takes several days. Payment process can be done in real time is a payment using Paypal. Paypal is a payment instrument that can foster the development of e-business. Paypal will make the small traders on the internet can receive payments from prospective buyers from overseas or make a payment when making transactions abroad through the Internet.